Tinjauan Yuridis Tindak Pidana Penyuapan oleh Pengusaha di Timor Tengah Utara Kepada Ketua Lembaga Swadaya Masyarakat dalam Tindak Pidana Korupsi Proyek Pembangunan Jalan Nona Manis di Kecamatan Biboki Anleu - Leonora Mathilda Safe; Bhisa Vitus Wihelmus; Orpa G. Manuain (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research is empirical juridical, with the aim of finding out the qualifications for regulating criminal acts of bribery committed by the head of a Non-Governmental Organization and to find out the criminal responsibility. The expected benefit of this research is that it can provide knowledge, can be an accurate source and become a reference for similar research. regarding the discipline of Criminal Law, especially Anti-Corruption Education.This result shows that the qualification of the regulation of criminal acts in the case of the chairman of the Non-Governmental Organization is contained in Article 23 of Law Number 31 of 1999 concerning the Eradication of Corruption and other criminal acts related to corruption. then the proof of the article of other criminal acts related to corruption, of which there are three articles that do not have to be accompanied by state losses. If it is connected with the Decision of the Constitutional Court Number 25 of 2016 specifically Article 2 and Article 3, the name of which is a formal offense to a material offense, it is mandatory that there must be state losses. But specifically Article 21, Article 22 and Article 23, the proof of his actions does not have to be a state loss because the qualification of the crime is a formal crime, not a material crime, so the change in mindset of the regulation and qualification of the crime in Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption from formal to material is only for Article 2 and Article 3. Criminal liability of the General Chairperson of the Anti-Corruption People's Alliance (ARAKSI) for committing a criminal act, with the existence of an unlawful act seen from the qualification of the regulation of the criminal act, then violating Article 23 of Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption